Seismic assessment of interacting structural units in complex historic masonry constructions by nonlinear static analyses. (March 2019) - Degli Abbati, Stefania; D'Altri, Antonio Maria; Ottonelli, Daria; Castellazzi, Giovanni; Cattari, Serena; de Miranda, Stefano; Lagomarsino, Sergio
Highlights: The seismic assessment of interacting masonry structures is challenging. We introduce a new numerical procedure based on nonlinear static analyses. From the modal analysis we define the dynamic response of each structural unit. Pushover load patterns are derived from the fitting of the modal shapes. The proposed procedure is validated on an earthquake-damaged fortress. Abstract: The damage occurred due to past earthquakes highlighted that the seismic behavior of historic masonry structures characterized by an aggregation of units with an own seismic behavior (e.g. palaces, fortresses, castles, etc.) is strongly affected by their dynamic interaction. At present, no codified and operational tools are available to perform the seismic assessment of such mutually interacting structures. This paper introduces a numerical procedure based on the use of nonlinear static analyses to fill this gap. The proposed procedure firstly requires the execution of a modal analysis on the 3D finite element model of the whole structure to define the modes which involve the dynamic response of each unit and their modal shapes. The latter are then fitted to define the load patterns to be applied on each unit through pushover analyses. The pushover curves obtained for each unit are then converted into capacity curves to finalize the seismic assessment. The effectiveness of the proposed procedure is shown through an application to a medieval fortress significantly damaged by the 2012 Emilia earthquake (Italy). The results achieved are promising and support the possible extension of the procedure to other typologies of complex historic structures composed by various interacting units.